On the Movement of Plants and the (Im)Possibility of Plant-and-Human Choreographies - Zamorska, Magdalena (Sensus Historiae, 2020)
New choreography tests possible embodiments and transcorporealities (Alaimo) facilitating becoming-plant (Deleuze, Guattari) and/or moving-together with plants. The author examines practices of Agata Siniarska, the choreographer, paying attention to plant-related practices and pondering over possibility of multispecies empathetic communication – a process of relating (Condit) and dynamic worldmaking. An empathetic translation of plant motivation into human behavioural language makes these processes possible. Conceptual and choreographic process envisages an egalitarian practice in which all parties involved retain and share the subject position.